HBM4EU E-waste study – An untargeted metabolomics approach to characterize metabolic changes during E-waste recycling - Lucyna Kozlowska; Susana Viegas; Paul T.J. Scheepers; Radu C. Duca; Lode Godderis; Carla Martins; Krzesimir Ciura; Karolina Jagiello; Maria João Silva; Selma Mahiout; Inese Mārtiņsone; Linda Matisāne; et al. (Environment International, 2025)
E-waste contains hazardous chemicals that may be a direct health risk for workers involved in recycling. We conducted an untargeted metabolomics analysis of urine samples collected from male e-waste processing workers to explore metabolic changes associated with chemical exposures in e-waste recycling in Belgium, Finland, Latvia, Luxembourg, the Netherlands, Poland, and Portugal. Questionnaire data and urine samples were obtained from workers involved in the processing of e-waste (sorting, dismantling, shredding, pre-processing, metal, and non-metal processing), as well as from controls with no known occupational exposure. Pre- and post-shift urine samples were collected and analysed using ultrahigh-performance liquid chromatography-mass spectrometry (UPLC-MS). A total of 32 endogenous urinary metabolites were annotated with a Variable Importance in Projection (VIP) above 2, indicating that e-waste recycling is mainly associated with changes in steroid hormone and neurotransmitter metabolism, energy metabolism, bile acid biosynthesis, and inflammation. The highest VIP was observed for dopamine-o-quinone, which is linked to Parkinson’s disease. These and other changes in metabolism in workers employed in the processing of e-waste need further verification in targeted studies.